2013
DOI: 10.5194/acp-13-7961-2013
|View full text |Cite
|
Sign up to set email alerts
|

WRF-Chem simulations in the Amazon region during wet and dry season transitions: evaluation of methane models and wetland inundation maps

Abstract: The Amazon region, being a large source of methane (CH4), contributes significantly to the global annual CH4 budget. For the first time, a forward and inverse modelling framework on regional scale for the purpose of assessing the CH4 budget of the Amazon region is implemented. Here, we present forward simulations of CH4 as part of the forward and inverse modelling framework based on a modified version of the Weather Research and Forecasting model with chemistry that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…We attribute the underprediction to a faster fall-off in modelled methane concentrations with altitude than that observed. To test this, we initially replaced the HadGEM2 model outputs above 400 hPa with methane mixing ratios derived from the thermal infrared (TIR) channel of the Tropospheric Emission Spectrometer (TES, AURA, 2004: Beer, 2006, because of its availability and ease of use. As discussed by Worden et al (2012), the CH 4 in the upper troposphere is biased high relative to the lower troposphere by 4 % on average.…”
Section: Initial Comparisonmentioning
confidence: 99%
“…We attribute the underprediction to a faster fall-off in modelled methane concentrations with altitude than that observed. To test this, we initially replaced the HadGEM2 model outputs above 400 hPa with methane mixing ratios derived from the thermal infrared (TIR) channel of the Tropospheric Emission Spectrometer (TES, AURA, 2004: Beer, 2006, because of its availability and ease of use. As discussed by Worden et al (2012), the CH 4 in the upper troposphere is biased high relative to the lower troposphere by 4 % on average.…”
Section: Initial Comparisonmentioning
confidence: 99%
“…Therefore, models are essential tools for understanding the interactions of physical and chemical processes that contribute to O 3 formation, as well as monitoring and predicting atmospheric chemistry composition, weather, and climate at local, regional, and global scales. In turn, the observations help constrain uncertainties in the model representations of parameterized convection, turbulence, land surface, and other subgrid scale processes that affect the simulated transport and chemical transformation of the atmospheric composition (Beck et al, 2013).…”
Section: M Bela Et Al: Ozone Production and Transport Over The Amentioning
confidence: 99%
“…However, the probability densities were consistent with observations in the boundary layer, indicating that horizontal dispersion was reasonable. Beck et al (2013) evaluated different CH 4 wetland emissions schemes and maps using WRF-GHG. They found the best agreement with BARCA CH 4 data for days when convective transport, as evaluated by comparison of upstream Tropical Rainfall Monitoring Mission (TRMM) and WRF precipitation amounts, was well represented in the model.…”
Section: Barca Aircraft Campaignsmentioning
confidence: 99%
“…A modelling study using synthetic CO 2 data by Mueller et al (2018) showed, that for the Baltimore-Washington area a substantial fraction of ~3 5% of the CO 2 background variability is caused by biogenic sources and sinks in July. Therefore, we simulate the biogenic CO 2 flux with the Vegetation Photosynthesis and Respiration Model (VPRM, Mahadevan et al, 2008) coupled with WRF-GHG (Beck et al, 2013) in order to estimate the influence of the photosynthetic uptake and respiration on our assessment of the anthropogenic flux. According to our analysis, the maximum daytime photosynthetic uptake predicted over the footprint area is at most 12% of the estimated anthropogenic flux.…”
Section: Discussion On Emission Fluxesmentioning
confidence: 99%